2023
DOI: 10.1002/jmv.28852
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis of long‐term sequelae of COVID‐19 2‐year after SARS‐CoV‐2 infection: A call to action for neurological, physical, and psychological sciences

Abstract: Long‐term sequelae conditions of COVID‐19 at least 2‐year following SARS‐CoV‐2 infection are unclear and little is known about their prevalence, longitudinal trajectory, and potential risk factors. Therefore, we conducted a comprehensive meta‐analysis of survivors' health‐related consequences and sequelae at 2‐year following SARS‐CoV‐2 infection. PubMed/MEDLINE, CENTRAL, and EMBASE were systematically searched up to February 10, 2023. A systematic review and meta‐analysis were performed to calculate the pooled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 44 publications
(141 reference statements)
1
32
0
Order By: Relevance
“…Emerging evidence from a pooled analysis of 1, 289, 044 study participants from 12 studies reports a 24.6% prevalence for impaired lung diffusion capacity among COVID-19 survivors up to 2 years after recovery from SARS-CoV-2 infection. 3 Similar evidence from a pooled analysis of 28 studies up to 6 months after recovery from SARS and MERS revealed impaired lung diffusion capacity at a prevalence of 27%. 74 However, a recent study by Peixun Zhang and colleagues followed up 71 healthcare workers for up to 15 years after recovery from SARS infection and reported that most recovery from pulmonary impairment occurred in the first 2 years (first year in 2003 = 9%; second year in 2004 = 3.2%) but persisted thereafter up to 15 years (15 th year in 2018 = 4.6%).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Emerging evidence from a pooled analysis of 1, 289, 044 study participants from 12 studies reports a 24.6% prevalence for impaired lung diffusion capacity among COVID-19 survivors up to 2 years after recovery from SARS-CoV-2 infection. 3 Similar evidence from a pooled analysis of 28 studies up to 6 months after recovery from SARS and MERS revealed impaired lung diffusion capacity at a prevalence of 27%. 74 However, a recent study by Peixun Zhang and colleagues followed up 71 healthcare workers for up to 15 years after recovery from SARS infection and reported that most recovery from pulmonary impairment occurred in the first 2 years (first year in 2003 = 9%; second year in 2004 = 3.2%) but persisted thereafter up to 15 years (15 th year in 2018 = 4.6%).…”
Section: Discussionmentioning
confidence: 66%
“…1 According to the Centre for Disease Control, long COVID is defined as a post-COVID-19 condition in which there is new, evolving or persistent health issues occurring ≥4 weeks after SARS-CoV-2 infection 2 Emerging evidence reports that fatigue (27.4%), anosmia (25%), impaired lung diffusion capacity (24.6%), alopecia (10.2%), and dyspnoea (10.1%) are the most frequent symptoms and findings in COVID-19 survivors 2 years after SARS-CoV-2 infection. 3 Lactate dehydrogenase (LDH) is a predominantly cytoplasmic (oxidoreductase) enzyme of cytosol of glycolytic cells and tissues; specifically, LDH catalyses the conversion of pyruvate to lactate using NADH (reduced nicotinamide adenine dinucleotide). 4 LDH also appears in the mitochondrial reticulum where it catalyses the oxidation of lactate to pyruvate for entry into the TCA Cycle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, it has the potential neurological and psychiatric features long established with RNA viruses such as influenza virus and, more recently, with coronaviruses [14,15]. Since scientific evidence is weak at this time [16][17][18][19][20], we strongly encourage clinical trials on long COVID with azithromycin to confirm or refute the value of this potentially efficient, cost-effective, readily available, easy-to-use, and relatively safe medication.…”
Section: Discussionmentioning
confidence: 99%
“…In another large Chinese cohort, 49% of COVID‐19 survivors had persistent symptoms after 12 months 2 . A meta‐analysis revealed that about 80% of patients who experienced an acute SARS‐CoV‐2 infection can develop one or more symptoms in the long‐term, 3 and up to 14.1% of them are still unable to return to work 2 years following the acute infection 4 . The most frequent clinical manifestations of long COVID are fatigue, dyspnea, chest discomfort, cough, anosmia, sleep difficulties, hair loss 4–12 .…”
Section: Introductionmentioning
confidence: 99%